Cambridge illustrated dictionary of astronomy - Mitton, Jacqueline 1948- (Cambridge University Press, 2007)
This lavishly illustrated new dictionary written by an experienced writer and consultant on astronomy provides an essential guide to the universe for amateur astronomers of all ages. Around 1300 carefully selected and cross-referenced entries are complemented by hundreds of beautiful colour illustrations, taken from space missions, the Hubble Space Telescope, and other major observatories on Earth and in space. Distinguished stellar illustrator Wil Tirion has drawn 20 new star maps especially for inclusion here. A myriad of named astronomical objects, constellations, observatories and space missions are described in detail, as well as biographical sketches for 70 of the most luminous individuals in the history of astronomy and space science. Acronyms and specialist terms are clearly explained, making for the most thorough and carefully assembled reference resource that teachers and enthusiasts of astronomy will ever need